Formula Optimization of Propolis Transfersome Gel, Aloe Vera, Gotu Extract: Formula Design, Formulation Evaluation and Cell Regeneration Test in Diabetic Wounds - Ajeng Puspo Aji; Rochany Septiyaningsih; Septiana Indratmoko; Elisa Issusilaningtyas; Solikhatun Nasikha (Postgraduate, University of Mataram, 2024)
The study was conducted to determine the optimal formula of transfersome propolis gel, aloe vera extract and gotu gotu leaf extract and test it against diabetic wounds in male white rats (Rattus norvegicus). The gel was created with an optimal formulation resulting from the application of a Design Expert with Cutimed as a positive control of burns on the backs of male white rats (Rattus norvegicus). Formula optimization was carried out using a Simple Lattice Design with variations of carbopol, TEA and glycerin. Activity tests of propolis transferosome gel, aloe vera extract and gotu gotu extract were conducted on 20 rats. The data results were statistically analyzed using the SPSS One Way ANOVA method. Phytochemical screening on aloe vera and gotu gotu showed the presence of flavonoid compounds, tannins and saponins. Transfersome propolis has a particle size of 88.55 nm and a zeta potential of -24.13 mV. The optimal formula produces a clear preparation in white, a distinctive odour, a stable viscosity of 19980 cps, dispersion power of 6.67 cm, adhesion of 4.07 seconds and pH of 6.45. The burn activity test had the fastest effectiveness on day 12 but did not differ significantly from the customized control.